2018
DOI: 10.1161/circulationaha.118.034338
|View full text |Cite
|
Sign up to set email alerts
|

Fully Automated Echocardiogram Interpretation in Clinical Practice

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
572
0
16

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 671 publications
(600 citation statements)
references
References 25 publications
12
572
0
16
Order By: Relevance
“…Knackstedt et al demonstrated that the left ventricular ejection fraction and longitudinal strain could be accurately and reproducibly computed from echo data using ML‐enabled software 17 . Zhang et al trained convolutional neural networks to obtain measurements of the left ventricle and predict various disease states including hypertrophic cardiomyopathy, cardiac amyloidosis, and pulmonary arterial hypertension 8 . While these studies demonstrate feasibility for utilization of ML approaches for LV functional assessment, there are limited data for its use for RV assessment, likely owing to the geometric complexity of RV structure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Knackstedt et al demonstrated that the left ventricular ejection fraction and longitudinal strain could be accurately and reproducibly computed from echo data using ML‐enabled software 17 . Zhang et al trained convolutional neural networks to obtain measurements of the left ventricle and predict various disease states including hypertrophic cardiomyopathy, cardiac amyloidosis, and pulmonary arterial hypertension 8 . While these studies demonstrate feasibility for utilization of ML approaches for LV functional assessment, there are limited data for its use for RV assessment, likely owing to the geometric complexity of RV structure.…”
Section: Discussionmentioning
confidence: 99%
“…Machine learning (ML)–based methodologies have the potential to provide fully automated image analysis. Conventional neural networks–based segmentation techniques have been applied to echo, though with focus primarily on left ventricular chamber size and systolic function quantification 8 . While a recent study examined a ML approach for three‐dimensional echocardiography (3DE) assessment of RV volume and EF, 9 limited clinical availability of 3DE is a known barrier for widespread utilization.…”
Section: Introductionmentioning
confidence: 99%
“…?B, a selection of the most common standard echocardiogram views were evaluated for model performance. Images from each study were classified using a previously described supervised training method 5 . We sought to identify the most information-rich views by training separate models on the subsets of dataset images of only one cardiac view.…”
Section: /14mentioning
confidence: 99%
“…Machine learning on echocardiography images can streamline repetitive tasks in the clinical workflow, standardize interpretation in areas with insufficient qualified cardiologists, and more consistently produce echocardiographic measurements.Related works Current literature have already shown that it is possible to identify standard echocardiogram views from unlabeled datasets. 5,6,24 Previous works have used convolutional neural networks (CNNs) trained on images and videos from echocardiography to perform segmentation to identify cardiac structures and derive cardiac function. In this study, we extend previous analyses to show that EchoNet, our deep learning model using echocardiography images, local cardiac structures and anatomy, estimate volumetric measurements and metrics of cardiac function, and predict systemic human phenotypes that modify cardiovascular risk.…”
mentioning
confidence: 99%
“…This would reduce inter-and intraobserver variability and create a unique quantification system in order to standardize diagnostic and monitoring scores. Such methodology, supported by artificialintelligence software, has been successfully tested for other ultrasound automated techniques [7]. The potential advantages in terms of faster data collection without increased costs and patients risks are intuitive.…”
mentioning
confidence: 99%